CYSTIC FIBROSIS RELATED DIABETES: CLINICAL CASES IN TERMS OF PRINCIPLES OF PEDIATRIC PALLIATIVE CARE - T. Chaychenko; M. Gonchar; G. Muratov; M. Kharkova; O. Rybka; N. Buginskaya; N. Shulga; T. Lutay; S. Dolgareva; N. Bashkirova (Ukrainian Journal of Translational Medicine (formerly Inter Collegas), 2018)
CYSTIC FIBROSIS RELATED DIABETES: CLINICAL CASES IN TERMS OF PRINCIPLES OF PEDIATRIC PALLIATIVE CAREChaychenko T., Gonchar M., Muratov G., Kharkova M., Rybka O., Buginskaya N., Shulga N., Lutay T.,  Dolgareva S., Bashkirova N. Cystic fibrosis related diabetes (CFRD)- is the most common comorbidity in people with cystic fibrosis , occurring in 20% of adolescents and 40–50% of adults. According to the Guidetothe Development of Children's Palliative Care Services life-limiting conditions may be delineated at four broad groups. Cystic fibrosis is a problem from group 2 - conditions where there may be long periods of intensive treatment aimed at prolonging life and allowing participation in normal childhood activities, but premature death is still possible.Basic aspects of CFRD were discussed, such as cause of the disease, genetic defects, differential diagnosis and principles of treatment. Two clinical cases of pediatric CFRD patients resented to highlight problems of management in terms of potential palliative care.According to our observations, patients with the CFRD, unfortunately, are perceived as patients with cystic fibrosis with no clear attention to diabetes. Both of them were presented with pure diabetes control due to unclear understanding CFRD with concomitant diet incompliance, irregular records, missed insulin injections, exercising limitations.We concluded that CFRD patients must be assessed by members of multidisciplinary team at CF centers, working by the principle of palliative care. There is necessary since the moment of CF diagnosing to involve endocrinologist and dietician due to of endocrine problems. Psychologist, social worker and well-trained educators are necessary to increase awareness of the CF comorbidities problem.Key words: Cystic fibrosis, cystic fibrosis related diabetes, pediatric palliative care, multidisciplinary team ДІАБЕТ, АСОЦІЙОВАНИЙ З МУКОВІСЦИДОЗОМ: КЛІНІЧНІ ВИПАДКИ З ТОЧКИ ЗОРУ ПРИНЦИПІВ ПЕДІАТРИЧНОЇ ПАЛІАТИВНОЇ ДОПОМОГИТ. Чайченко, М. Гончарь, Г. Муратов, М. Харькова, О. Рибка, Н. Бужинская, Н. Шульга, Т. Лутай, С. Долгарева, Н. БашкіроваЦукровий діабет асоційований з муковісцидозом - найбільш поширене ускладнення у осіб, що страждають на муковісцидоз, яке реєструється у 20% підлітків та 40-50 % дорослих. Відповідно до рекомендацій з надання паліативної допомоги дітям, умови для обмеження життя можуть бути визначені у чотирьох широких групах. Муковісцидоз є проблемою, що відноситься до другої групи - стани, при яких передчасна смерть неминуча, але тривале інтенсивне лікування може збільшити тривалість життя дитини і дозволить зберегти якість і фізичну активність.В статті обговорено основні поняття про цукровий діабет асоційований з муковісцидозом, такі як причини захворювання, генетичні дефекти, диференційний діагноз та принципи лікування. Два клінічних випадки педіатричних пацієнтів розглянуто з метою вивчення проблем лікування  з точки зору потенційної паліативної допомоги.Згідно з нашими спостереженнями, пацієнти з цукровим діабетом асоційованим з муковісцидозом, сприймаються як пацієнти з муковісцидозом без чіткої уваги до діабету. Обидва пацієнти не мали адекватного глікемічного контролю із-за нечіткості розуміння проблеми, що призводило до недотримання дієти, нерегулярності записів у щоденниках самоконтролю, пропущені ін'єкцій інсуліну.Ми прийшли до висновку, що пацієнти з цукровим діабетом асоційованим з муковісцидозом мають спостерігатися членами міждисциплінарної команди в спеціалізованих центрах, що функціонують за принципом паліативної допомоги. Починаючи з моменту діагностики муковісцидозу до таких команд необхідно залучати ендокринолога та дієтолога із-за високого ризику ендокринних розладів. Психолог, соціальний працівник та добре навчені педагоги необхідні для підвищення обізнаності про проблему та супутні захворювання.Ключові слова: муковісцидоз, цукровий діабет асоційований з муковісцидозом, дитяча паліативна допомога, міждисциплінарна командаДИАБЕТ, АССОЦИИРОВАННЫЙ С МУКОВИСЦИДОЗОМ: КЛИНИЧЕСКИЕ СЛУЧАИ С ТОЧКИ ЗРЕНИЯ ПРИНЦИПОВ ПЕДИАТРИЧЕСКОЙ ПАЛІАТИВНОЙ ПОМОЩИТ. Чайченко, М. Гончарь, Г. Муратов, М. Харькова, О. Рыбка, Н. Бужинская, Н. Шульга, Т. Лутай, С. Долгарева, Н. БашкироваСахарный диабет, ассоциированный с муковисцидозом - наиболее распространенное осложнение у лиц, страдающих муковисцидозом, которое регистрируется у 20 % подростков и 40-50 % взрослых. В соответствии с рекомендациями по оказанию паллиативной помощи детям, условия для ограничения жизни могут быть определены в четырех широких группах. Муковисцидоз является проблемой, которая относится ко второй группе - состояния, при которых преждевременная смерть неизбежна, но длительное интенсивное лечение может увеличить продолжительность жизни ребенка и позволит сохранить качество и физическую активность.В статье обсуждены основные понятия о сахарном диабете ассоциированного с муковисцидозом, такие как причины заболевания, генетические дефекты, дифференциальный диагноз и принципы лечения. Два клинических случая педиатрических пациентов рассмотрено с целью изучения проблем лечения с точки зрения потенциальной паллиативной помощи.Согласно нашим наблюдениям, пациенты с сахарным диабетом ассоциированным с муковисцидозом, воспринимаются как пациенты с муковисцидозом без четкой внимания к диабету. Оба пациента не имели адекватного гликемического контроля из-за нечеткости понимания проблемы, что приводило к не соблюдению диеты, не регулярности записей в дневниках самоконтроля, пропущенных инъекций инсулина.Мы пришли к выводу, что пациенты с сахарным диабетом ассоциированным с муковисцидозом должны наблюдаться членами междисциплинарной команды в специализированных центрах, которые функционируют по принципу паллиативной помощи. Начиная с момента диагностики муковисцидоза к таким командам необходимо привлекать эндокринолога и диетолога из-за высокого риска эндокринных расстройств. Психолог, социальный работник и хорошо обученные педагоги необходимы для повышения осведомленности о проблеме и сопутствующих заболеваниях.Ключевые слова: муковисцидоз, сахарный диабет ассоциированный с муковисцидозом, детская паллиативная помощь, междисциплинарная команда